Mediatization and the Disproportionate Attention to Negative News: The case of airplane crashes. (26th April 2019) - van der Meer, Toni G. L. A.; Kroon, Anne C.; Verhoeven, Piet; Jonkman, Jeroen
Abstract : Do news media increasingly portray a distorted world image when reporting menace? The purpose of this study is to investigate how media attention for negative incidents evolves over time and how this relates to real-world trends and public responses. A longitudinal content analysis (1991–2015) of media coverage of aviation incidents is used to provide a systematic investigation into the trends of media attention related to real-world data. Results show that while the total number of aviation incidents declined across time, relative media attention increased. Time series analysis revealed that media attention for these negative incidents was negatively associated with shifts in public responses—i.e. air travel behavior—whereas real-world statistics on aviation incidents did not seem to explain variation in public behavior. Moreover, when exploring the variation in the coverage of media attention, increasing presence of mediatization facets was observed as a potential explanation for the over-time rise in disproportional attention to negative news. In conclusion, news media may have a blind spot for progression and a distorted media reality can be a predictor of public responses instead of reality itself.